PENINGKATAN SUMBER DAYA MANUSIA POLRI SEBAGAI KUNCI KEBERHASILAN RESTORATIVE JUSTICE - Ardiansyah, Deni; Noor, Marzuki (The Juris, 2024)
This study examines the application of the concept of restorative justice in the Indonesian criminal justice system, particularly in the context of the Draft Criminal Code (RUU KUHP). The purpose of this research is to analyze the challenges and potential of implementing the principles of restorative justice in the criminal law process in Indonesia, as well as to provide recommendations for its application. The method used is a descriptive qualitative approach combined with normative legal analysis, involving the analysis of legal documents and empirical data collection through interviews and documentation studies. The findings of the study indicate that although this concept holds great potential for creating more humane justice, its implementation is still hindered by public perception, lack of competency among law enforcement officers, and regulatory ambiguity. This study recommends enhancing the mediation competencies of law enforcement officers, as well as the need for clearer regulations regarding the application of restorative justice. Furthermore, public awareness and support are crucial for the successful implementation of this approach in resolving criminal cases.